1996
DOI: 10.1007/bf03011721
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis following a combined spinalepidural technique in a labouring term parturient

Abstract: Meningitis following a combined spinalepidural technique in a labouring term parturient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…However, this intuitive argument is not supported by any clinical series and there is very likely to be a publication bias as authors and editors might tend to publish complications of a recent rather than a well-known technique (epidural or spinal). The present case has many clinical features in common with those reported by Cascio et al [5] and Aldebert et al [6]. In all these cases the anaesthetist wore a gown, a cap, a face mask and sterile gloves, symptoms appeared early and diagnosis was made within 24 h of the CSE.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, this intuitive argument is not supported by any clinical series and there is very likely to be a publication bias as authors and editors might tend to publish complications of a recent rather than a well-known technique (epidural or spinal). The present case has many clinical features in common with those reported by Cascio et al [5] and Aldebert et al [6]. In all these cases the anaesthetist wore a gown, a cap, a face mask and sterile gloves, symptoms appeared early and diagnosis was made within 24 h of the CSE.…”
Section: Discussionsupporting
confidence: 84%
“…Cascio et al [5] postulated that the Streptococcus salivarius isolated from their patient's CSF was a contaminant because it only grew in a single broth culture and also Anaesthesia, 1998, 53, 290-295 Case reports . ............................................................................................................................................................................................................................................... because it is not a bacterial pathogen that commonly causes meningitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, judging by the numbers of published cases, it could be the second commonest neurological complication of neuraxial analgesia in labour, after paraesthesiae. Loo et al 6 found 20 cases, 31,[43][44][45][46][47][48][49][50][51][52][53][54] while at least seven others [55][56][57][58][59][60][61] and one case of Herpes simplex encephalitis 62 among parturients, and dozens more among non-obstetric patients, have been reported since.…”
Section: Sources Of Infectionmentioning
confidence: 98%
“…However, since 1994 there have been two case reports of aseptic meningitis involving the needlethrough-needle technique [4,5]. Concerning both of these reports, we have commented on the possibility that these metallic microparticles should be considered in the differential diagnosis.…”
mentioning
confidence: 93%